2009
DOI: 10.1039/b915838c
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical performance of graphene nanosheets and ceramic composites as anodes for lithium batteries

Abstract: A nanocomposite anode material for lithium batteries is designed and fabricated by the insertion of graphite nanosheets (GNS) into the ceramic network of silicon oxycarbide (SiOC) ceramics for the development of structurally and electrochemically stable lithium batteries. The GNS forms a layered phase in the SiOC ceramic network from the self-assembly of graphite oxides (GO) introduced in a polysiloxane precursor through thermal transformations after pyrolysis. The composite anode (GNS/ SiOC) exhibits an initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(64 citation statements)
references
References 14 publications
1
62
1
Order By: Relevance
“…Indeed, it was subsequently found that, in absence of binder, the 1 st cycle irreversible specifi c capacity was always higher than 40% [37][38][39][40][41] and, in some cases, the binder-free electrodes were very fragile and diffi cult to handle. [ 41 ] Despite few research efforts starting the good practice of reporting the electrodes' active material loadings, [ 35,42 ] still the focus was only on gravimetric capacity, and no indication on volumetric values was given. Thus, making even harder a fair estimation of RGO potential as LIB anode.…”
Section: Continuedmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it was subsequently found that, in absence of binder, the 1 st cycle irreversible specifi c capacity was always higher than 40% [37][38][39][40][41] and, in some cases, the binder-free electrodes were very fragile and diffi cult to handle. [ 41 ] Despite few research efforts starting the good practice of reporting the electrodes' active material loadings, [ 35,42 ] still the focus was only on gravimetric capacity, and no indication on volumetric values was given. Thus, making even harder a fair estimation of RGO potential as LIB anode.…”
Section: Continuedmentioning
confidence: 99%
“…Other two kinds of graphene hybrid were also reported in the same year, namely, RGO-cuprous oxide [ 110 ] and RGO-silicon oxycarbide. [ 42 ] Unluckily, none of these demonstrated substantially enhanced electrochemical properties compared to graphite (see Table 2 ). In spite of the not exciting performance, in their research effort, F. Hou et al [ 42 ] highlighted the impact of the composite preparation method on its lithium-storage properties.…”
Section: Graphene-containing Materials As a Li-ion Hostsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous materials have been investigated and used as electrodes of supercapacitors; they can mainly be divided into three types: (i) carbonaceous materials, (ii) conducting polymers, and (iii) transition metal oxides [5][6][7][8]. Among the possible materials, transition metal oxides were studied extensively, such as MnO 2 , Co 3 O 4 , ZnO, and so on [9][10][11][12][13][14][15][16][17][18]. Layered double hydroxide (LDH) as a kind of heterostructure nanomaterials have shown superior properties in applications such as catalysis, sorption, medicine, and so on [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…This kind of carbon material possesses a long cycle life and good mechanical properties. Metal oxides (MnO 2 , Co 3 O 4 , RuO 2 ) and conducting polymers (polyaniline, polypyrrole and polythiophene) [10][11][12][13][14][15][16][17][18] are typical pseudocapacitive materials that can achieve relatively high capacitance but are limited by poor cyclability due to structural degradation of the electrode through the redox process. 19,20 So the capacitance can be enhanced by incorporating carbon materials with pseudocapacitive materials.…”
Section: Introductionmentioning
confidence: 99%